Fun English pictures to improve students’ simple communication ability - Elisa Dewi Kusumawati (Universitas Sarjanawiyata Tamansiswa, 2019)
The objective of the research is to improve the third grade students’ simple communication ability of SD Muhammadiyah Macanan in the academic year of 2017/2018 with the use of Fun English Pictures media. It was expected that Fun English Pictures could improve the students’ simple communication ability. Based on the observation, there were some problems in the teaching and learning of simple communication. To solve those problems, the researcher implemented Fun English Pictures as a learning media. The research was carried out through action research that consisted of two cycles. The researcher collaborated with the English teacher in implementing the actions and an observer. The data were in the forms of qualitative. The qualitative data were in the forms of field notes, observation sheet, interview transcripts, and photographs. The validity used were democratic validity, outcome validity, process validity, catalytic validity and dialogic validity. The reliability used was time triangulation and investigator triangulation. The steps of the research were reconnaissance, planning, action and observation and reflection. The research found that: (1) Fun English Pictures can improve students’ simple communication ability and can help them to speak confidently, (2) the use of Fun English Pictures can give the students more chances for practicing simple communication, and therefore the students can lose their fears of making mistakes and be more confident, (3) the use of Fun English Pictures can improve the students’ fluency, pronunciation, vocabulary and accuracy.